2010
DOI: 10.1051/0004-6361/201014094
|View full text |Cite
|
Sign up to set email alerts
|

Circumstellar molecular composition of the oxygen-rich AGB star IK Tauri

Abstract: Context. Molecular lines in the (sub)millimeter wavelength range can provide important information about the physical and chemical conditions in the circumstellar envelopes around asymptotic giant branch stars. Aims. The aim of this paper is to study the molecular composition in the circumstellar envelope around the oxygen-rich star IK Tau. Methods. We observed IK Tau in several (sub)millimeter bands using the APEX telescope during three observing periods. To determine the spatial distribution of the 12 CO(3−2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
46
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(57 citation statements)
references
References 33 publications
(70 reference statements)
9
46
2
Order By: Relevance
“…The angular diameter is estimated around 20 mas (Decin et al 2010a). Currently, a dozen different molecules and some of their isotopologues have been discovered in IK Tau, including CO, HCN, SiO, SiS, SO, SO 2 , NaCl, NS, NO, HCO + , H 2 CO, PO, PN, and H 2 S (Milam et al 2007;Kim et al 2010;Decin et al 2010a,b;De Beck et al 2013Velilla Prieto et al 2017). Some molecules including SiO and SiS are depleted in the circumstellar envelope, possibly owing to condensation onto dust grains.…”
Section: Target Selectionmentioning
confidence: 99%
“…The angular diameter is estimated around 20 mas (Decin et al 2010a). Currently, a dozen different molecules and some of their isotopologues have been discovered in IK Tau, including CO, HCN, SiO, SiS, SO, SO 2 , NaCl, NS, NO, HCO + , H 2 CO, PO, PN, and H 2 S (Milam et al 2007;Kim et al 2010;Decin et al 2010a,b;De Beck et al 2013Velilla Prieto et al 2017). Some molecules including SiO and SiS are depleted in the circumstellar envelope, possibly owing to condensation onto dust grains.…”
Section: Target Selectionmentioning
confidence: 99%
“…Chemical abundance stratifications are coupled to theoretical non-equilibrium (non-TE) predictions in the outer envelope by Willacy & Millar (1997) and compared to the shock-induced non-TE inner wind predictions by Duari et al (1999) and Cherchneff (2006). The star IK Tau has been chosen for study because of the wealth of observations which are available for this target and because its envelope is thought to be (roughly) spherically symmetric (Lane et al 1987;Marvel 2005;Hale et al 1997;Kim et al 2010). …”
Section: Integrated Line Intensities Are Often Used As a Criterion Tomentioning
confidence: 99%
“…Several authors have derived new constraints on chemical and circumstellar models based on the simplifying assumption of unresolved optically thin emission thermalized at one excitation temperature (e.g. Lindqvist et al 1988;Omont et al 1993;Bujarrabal et al 1994;Kim et al 2010). (3.)…”
Section: Introductionmentioning
confidence: 99%
“…It has a period of 500 days (Kukarkin et al 1971), and a fairly high massloss rate of 1 × 10 −5 M yr −1 (Ramstedt et al 2008). The star has a rich circumstellar chemistry, as indicated by the detection of a large number (>20) of different molecular species (see e.g., Kim et al 2010;Decin et al 2010, for the latest results). The circumstellar gas distribution has been mapped in CO(J = 1 → 0), CO(J = 2 → 1) (Castro-Carrizo et al 2010), and CO(J = 3 → 2) (Kim et al 2010) emission.…”
Section: Introductionmentioning
confidence: 99%
“…The star has a rich circumstellar chemistry, as indicated by the detection of a large number (>20) of different molecular species (see e.g., Kim et al 2010;Decin et al 2010, for the latest results). The circumstellar gas distribution has been mapped in CO(J = 1 → 0), CO(J = 2 → 1) (Castro-Carrizo et al 2010), and CO(J = 3 → 2) (Kim et al 2010) emission. Castro-Carrizo et al (2010 found a western elongation in its innermost region (of ∼1000 AU), and on larger scales a flattened circumstellar envelope that is elongated in the east-west plane over ∼10 000 AU.…”
Section: Introductionmentioning
confidence: 99%